2022
DOI: 10.3389/fonc.2022.780950
|View full text |Cite
|
Sign up to set email alerts
|

Derivation, Comprehensive Analysis, and Assay Validation of a Pyroptosis-Related lncRNA Prognostic Signature in Patients With Ovarian Cancer

Abstract: BackgroundPyroptosis is regulated by long non-coding RNAs (lncRNAs) in ovarian cancer (OC). Therefore, a comprehensive analysis of pyroptosis-related lncRNAs (PRLs) in OC is crucial for developing therapeutic strategies and survival prediction.MethodsBased on public database raw data, mutations in the landscape of pyroptosis-related genes (PRGs) in patients with OC were investigated thoroughly. PRLs were identified by calculating Pearson correlation coefficients. Cox and LASSO regression analyses were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…For treating autoimmune diseases, TNFRSF1B is a powerful therapeutic target ( 34 ). Recently, AC007991.4 was shown to be associated with the prognosis of gastric and ovarian cancer ( 35 , 36 ), while LINC00996 can be used as a prognostic factor for colorectal and lung cancer ( 37 , 38 ). There are no published studies related to AL133371.2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For treating autoimmune diseases, TNFRSF1B is a powerful therapeutic target ( 34 ). Recently, AC007991.4 was shown to be associated with the prognosis of gastric and ovarian cancer ( 35 , 36 ), while LINC00996 can be used as a prognostic factor for colorectal and lung cancer ( 37 , 38 ). There are no published studies related to AL133371.2.…”
Section: Discussionmentioning
confidence: 99%
“…AC011445.1 is related to SIRT2 and SPATA2. SIRT2 is an NAD+-dependent deacetylase and is the only sirtuin protein found in the cytoplasm, mitochondria, and nucleus [36]. It can regulate autophagy in high-fat-exposed immune cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…This study constructed a ceRNA network mediated by the MIR600HG/hsa-mir-21-5p axis and included five targeting mRNAs (BCL11B, ETS1, EPHA4, KLF12, and KMT2A). A few studies have demonstrated the function of MIR600HG, which is considered a lncRNA biomarker for predicting the progression of tumor patients ( Song et al, 2018 ; Cao et al, 2022 ). Xiao et al (2021 ) reported that MIR600HG, which was involved in the ceRNA network in the present study, influenced pancreatic adenocarcinoma progression by regulating immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The ten lncRNAs with the largest differences (FTX, ENTPD1-AS1, AL365361.1, OIP5-AS1, SNAI3-AS1, AL132656.2, PSMD6-AS2, MALAT1, POLR2J4, and WDFY3-AS2) were then further analyzed. Except for AL132656.2, all other lncRNAs have been reported to be associated with cancers (39)(40)(41)(42)(43)(44)(45)(46)(47). However, no studies have reported that these lncRNAs play a specific role in SKCM.…”
Section: Construction Of the Lncrna-mirna-mrna Triple Regulatory Networkmentioning
confidence: 99%